Encyclopedia Brown and the case of the disgusting sneakers - Sobol, Donald J., 1924-; Owens, Gail. (New York : Yearling/Random House, 2002)
America's Sherlock Holmes in sneakers continues his war on crime in ten more cases, the solutions to which are found in the back of the book.
Keywords: Mystery and detective stories; Literary recreations